UI/UX Design Using the Design Thinking Method in the Development of a New Student Registration Information System Website at Raudhatul Athfal (RA) Qurrotul 'Uyun - Adinda Gita Lestari; Findi Ayu Sariasih; Edhi Prayitno; Chaerul Bahri; Chandra Setiawan (Publikasi Indonesia, 2025)
This research aims to design User Interface (UI) and User Experience (UX) for website-based student registration at Raudhatul Athfal (RA) Qurrotul 'Uyun using design thinking method. In the face of educational development and the need for technological innovation, the use of technology in school administration activities is crucial to improve efficiency. This research highlights the problems faced by Raudhatul Athfal Qurrotul 'Uyun, namely the use of manual forms and Google Forms in Registration, which have the potential to result in filling errors and difficult data management. The design thinking method is applied through the stages of empathize, define, ideate, prototype, and testing. Interviews were conducted with prospective student guardians, solution ideas were collected, and a UI design was created to illustrate user flow. The prototype was tested through usability testing with the system usability scale, involving 12 respondents. The results showed that the UI and UX design of web-based student registration using figma tools with the design thinking method can be done at Raudhatul Athfal (RA) Qurrotul 'Uyun.